Game-Based Educational Media: Comparison of Puzzles and Qugisaki in Improving Dental Health Knowledge - Ulliana, Ulliana; Setyawati, Baby Prabowo; Jannah, Miftahul; Barka, Amani A (Yayasan Ahmad Mansyur Nasirah, 2025)
Dental health issues need to be a global concern, almost half of the world's population suffers from dental and oral diseases. The DMF-T Index for primary school age children in Indonesia shows a decline from 7.1% to 5.4% in 2018 to 2023. But the severity falls into the high to very high category. Dental health education from an early age is very important to form habits that continue into adulthood. The use of game-based learning media such as puzzles and qugisaki can be one of the interesting and interactive educational alternatives. This study aims to find out the difference in the level of knowledge of grade IV students before and after being given dental health education using the media of puzzle games and qugisaki (Quartet Gigi Masa Kini). The research method is an experimental method with a pre-test and post-test design. The sampling technique used in this study is a total sampling of 64 students. The measurement was carried out by comparing the knowledge scores of pretest and post-test students after treatment using nonparametric statistical tests. The results showed that a significant increase in knowledge was obtained after being educated with puzzle and qugisaki media, with a p-value of 0.000 (<0.01). The average score of students' knowledge increased from 17.50 to 18.34 in puzzle media and 16.81 to 17.72 in qugisaki media. The analysis of the Man-Whitney test shows that there is a significant difference between the two media with a p-value of 0.049 (<0.05). Puzzle media has been proven to be more effective in increasing students' knowledge than qugisaki media and can be used as a dental health education tool. This research is expected to be developed into educational media such as augmented reality (AR) or educational game-based applications.